2014
DOI: 10.4236/tel.2014.42020
|View full text |Cite
|
Sign up to set email alerts
|

Price and Quantity Competition in a Mixed Duopoly with Emission Tax

Abstract: This paper compares price and quantity competition in a mixed duopoly with emission tax; in a mixed duopoly, one public firm competes with one private firm in the market. We find that social welfare is the highest when both the firms simultaneously choose price levels. Then, the optimal emission tax is sufficiently lower than the marginal social damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…of the profits of the foreign private firm (Fernandez-Ruiz [3]). Furthermore, our paper focuses on the managerial aspect of the firms.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…of the profits of the foreign private firm (Fernandez-Ruiz [3]). Furthermore, our paper focuses on the managerial aspect of the firms.…”
Section: The Modelmentioning
confidence: 99%
“…In this case, there is a manager at each firm. In the third stage, the public firm's manager and the foreign private firm's manager choose the output that maximizes respectively (4) and (3). Solving these problems, we obtain: λ that maximizes respectively (1) and (2).…”
Section: Both Firms Hire Managers (Dd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the literature provided numerous perspectives on sustainable energy and ECSR. However these studies are mainly concerned the impacts of firm behavior on environment regulations in a mixed oligopoly [20,21]. Nowadays, with the rapid development of economy, the ecological environment is deteriorating, and a sustainable development calls for the innovation of green technology [22].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent papers have demonstrated that the rankings of quantities, prices, profits, and welfare are sensitive to assumptions on the number of firms and symmetry of cost and demand parameters (e.g., Häckner, 2000;Zanchettin, 2006). More recently, a number of papers have turned to mixed duopoly where a public, welfare-maximizing firm competes against a private, profit-maximizing firm (e.g., Ghosh and Mitra, 2010;Scrimitore, 2011Scrimitore, , 2013Choi, 2012aChoi, , 2012bMatsumura and Ogawa, 2012;Andree, 2013;Chirco et al, 2013;Nakamura, 2013;Ohori, 2013). Taken together, the papers of Matsumura and Ogawa (2012) and Ghosh and Mitra (2010) provide a (partial) characterization of the effect on the market variables and profits.…”
Section: Introductionmentioning
confidence: 99%